Tom Thomson, Antimodernism, and the Ideal of Manhood - Cameron, Ross (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1999)
AbstractTom Thomson is a legendary figure in Canadian culture. That legend was created after his death by a group of colleagues and admirers, many of whom had or later took up central positions in Canadian art circles and were important contributors to the nationalist movement of interwar Canada. Thomson's mythologisers created a symbol and a myth which combined their concerns about modernity - its threats to manhood and to Canadian society - and their desire to build a national cultural hero out of their own experiences. But their antimodern enthusiasm for the wilderness vacation also reinforced - though with a newly enthusiastic emphasis - an existing definition of Canada as an untamed country filled with rugged, virile men. In the face of the challenges of modernity, the Thomson of legend revitalized the independent and virile manhood his celebrants considered to be essential aspects of the national identity.